Lower Urinary Tract and Gastrointestinal Dysfunction Are Common in Early Parkinson’s Disease - Daniel Martinez-Ramirez; Edna Sophia Velazquez-Avila; Alejandro Almaraz-Espinoza; Arnulfo Gonzalez-Cantú; Genaro Vazquez-Elizondo; Daniel Overa-Posada; Amin Cervantes-Arriaga; Mayela Rodriguez-Violante; Mirna Gonzalez-Gonzalez (Parkinson's Disease)
Purpose. Autonomic dysfunction is a common nonmotor feature and early manifestation of Parkinsons disease (PD). Autonomic dysfunction in PD is associated with a worse prognosis. We sought to characterize autonomic dysfunction and identify associated factors in patients with early PD. Methods. An observational, cross-sectional, descriptive, and analytical study was conducted to evaluate patients with early PD from the Parkinsons Progression Markers Initiative. We utilized the Scales for Outcomes in Parkinsons Disease-Autonomic dysfunction questionnaire to determine the prevalence and frequencies of autonomic symptomatology. The cohort was grouped into high and low dysautonomic scores. A regression model identified variables that independently explained dysautonomic scores in our early PD cohort. Results. 414 PD patients had a mean age of 61.1 (SD 9.7) years at diagnosis and mean disease duration of 6.7 (SD 6.6) months. Among all patients, 43.7% (181/414) had high dysautonomic scores. Urinary and gastrointestinal symptoms were the most prevalent and frequently reported dysautonomic symptoms. Patients with fatigue (beta = 4.28, p<0.001), probable rapid eye movement sleep behavior disorder (beta = 2.71, p<0.001), excessive daytime sleepiness (beta = 1.88,p=0.039), impulsivity and compulsivity (beta = 2.42, p<0.001), and increasing age (beta = 1.05, p<0.001) were more likely to have high dysautonomic scores. Conclusion. Lower urinary tract and gastrointestinal symptoms are prevalent and frequent in early PD patients. Fatigue, sleep disorders, impulsivity and compulsivity, and age are predictors of autonomic dysfunction. Autonomic symptoms predominated in this group of early PD patients in the disease course and were associated with more severe disease.